Strategies for Teaching Speaking Skills According to Behavioral Theory in the Intensive Programs l Astiratijiyah Ta’lim Maharat al-Kalam ‘ala Dau' al-Nazariyah al-Sulukiyah fi al-Barnamaj al-Mukatsaf - Ihwan, Muhamad Bisri; Hamid, Muhammad Abdul; Himmah, Ro'fat Hizmatul; Mufauwiq, Mukhtar Nabali (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2024)
Education plays an important role in human behavior to improve the quality of life, so there must be mature thought for the success of education. To produce a good education there needs to be an educational strategy, therefore an educational strategy is very important. This study aimed to reveal the forms of strategies for teaching speaking skills in terms of behavioral theory in the intensive program and reveal the contribution of implementing speaking skills teaching strategies in intensive programs at the Darussalam Banyuwangi Islamic Religion Institute. In this study, researchers used a qualitative approach and methodology as a case study in the Arabic Language Education Department. Used for collecting teacher and student interview data in the Intensive Program, classroom and outside classroom observations and documentation. Using interactive data analysis. The method of checking the validity of the data is by triangulation of theory and sources. The results of this study in essence are: (1) The strategies for teaching speaking skills in the perspective of behavioral theory in the intensive program are strategies of repetition and memorization, storytelling strategies, strategies for presenting modern topics, and strategies for creating an artificial Arabic environment. (2) The contribution of implementing speaking skills teaching strategies in the intensive program is the high demand for teaching Arabic and the ease of teaching Arabic, and the Institute has become famous for Arabic.